Claiming spaces: British Muslim negotiations of urban citizenship in an era of new migration. Issue 1 (31st March 2014) - Phillips, Deborah
<x xml:space="preserve">Abstract</x> This paper seeks to complicate understandings of British Muslim citizenship that have so far largely been framed in terms of British Muslim negotiations with the majority white British population and its institutions. Building on the notion of the city as a lived space, the paper explores how, in an era of growing international migration and social difference, everyday negotiations between British Muslims and new migrants bring formal constructions of citizenship (as status) and the performative expression of citizenship (as a lived experience and the practice of belonging) to the fore. Inspired by the work of theorists on urban citizenship, living with difference and emerging constructions of emotional citizenship, the paper underscores the salience of the neighbourhood as a performative space implicated in citizenship formation and the sedimentation of feelings of belonging. Drawing on encounters between established British Muslims and new Eastern European migrants to Bradford, the paper emphasises the significance of neighbourhood as a site of struggle, citizenship claims, and a social, political and emotional space of citizen formation at a time of geopolitical change. Central to the argument are the challenges posed to British Muslims' understandings of 'self as citizen' that arise from encounters with mobile, white, Christian bodies settling in spaces appropriated and marked as Muslim. The findings engage with debates about the place of British Muslims in shifting constructions of British citizenship and explore implications for politicised discourses on community, security, integration and the capacity to live with difference for those who are all too often discursively cast as 'not good enough' British citizens.